The protective effects of Anakinra in a neonatal rat model of necrotizing enterocolitis - Gunes, Hatice; Ipek, Sevcan; Yurttutan, Sadik; Kuloglu, Tuncay; Tolun, Fatma; Kazanci, Ulku; Doganer, Adem (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: Necrotizing enterocolitis (NEC) is a commonly seen life-threatening condition in newborns characterized by ischemic necrosis. This study aimed to investigate anakinras effects, an interleukin-1 receptor antagonist, on oxidative stress, inflammation, and tissue necrosis in an NEC rat model. Materials and methods: Forty Wistar albino pups were divided into four groups randomly as follows; group 1, control group; group 2, anakinra-treated control group; group 3, NEC group; and group 4, NEC and anakinra treatment group. The rats were given hyperosmolar formula feeding, and they were exposed to hypoxia after cold stress at +4 degrees C and oxygen in order to create the NEC model. On the 4th day of the experiment, the pups were decapitated, and the intestinal tissues were resected for biochemical and histopathologic examination. Results: Microscopic injury scores and apoptotic indexes were higher in group 3 than the control group (p < 0.001, p = 0.002, respectively), and there was a significant decrease after anakinra. Interleukin 18 and caspase-3 levels increased with NEC and decreased significantly after administration of anakinra (p = 0.006, p = 0.004, respectively). Malondialdehyde and glutathione peroxidase levels also increased compared with the control group (p = 0.019, p = 0.002, respectively). Conclusion: In this experimental study, we found that anakinra had antiinflammatory and antioxidant effects and was protective against intestinal injury and apoptosis.
Keywords: Anakinra; apoptosis; caspase-3; interleukin 18; necrotizing enterocolitis; rat